The MOOC and the Multitude. Issue 3 (June 2016) - Curinga, Matthew X.
Abstract: Massive open online courses (MOOCs) take university lectures and other educational materials and make them available for free as online "courses." Liberal and neoliberal MOOC supporters laud these courses for opening up education to the world while incorporating market dynamics to improve quality and drive down costs. Skeptics claim MOOCs are a bald attempt to privatize higher learning, thus creating an apartheid educational system with traditional universities serving the wealthy while everyone else is left with cut‐rate online learning. This essay draws on the political theory of autonomist Marxism, arguing that MOOCs are capital's defensive reaction to the threats of resistant universities on one side, and unmanageable Internet‐based learning on the other. It then looks at which MOOC designs would support education for the "multitude, " which is the term used by autonomist Marxism to describe an autonomous, diverse, networked political body.